Pemanfaatan Nanoteknologi Dalam Pengembangan Material Ramah Lingkungan - Afriansyah (CV. SINAR HOWUHOWU, 2025)
Intense pressure on the global environment is driving an urgent need for environmentally friendly materials. Nanotechnology has emerged as a transformative technological platform offering innovative solutions to this challenge. This article aims to systematically review the applications, potential, and challenges of nanotechnology in the development of environmentally friendly materials. Using a systematic literature review approach, this study analyzes relevant literature published over the past decade. The analysis reveals that nanotechnology contributes significantly through three primary pathways: (1) enhancing bio-based nanocomposites to replace conventional plastics, (2) creating functional surfaces for energy efficiency and resource conservation, and (3) developing advanced nanomaterials for pollution remediation and green chemistry applications. However, beyond this potential, the study also identifies crucial challenges related to potential nanotoxicity and life cycle impacts (Life Cycle Assessment/LCA), which require careful evaluation to ensure the holistic sustainability of the resulting materials. In conclusion, nanotechnology is a vital enabler, yet its application demands a responsible and integrated approach to innovation to ensure that technological solutions do not create new ecological problems.